Pengaruh Akuntabilitas Keuangan Daerah, Value For Money, Kejujuran, Transparansi, Dan Pengawasan Terhadap Pengelolaan Keuangan Daerah (Studi Kajian Pada Pemerintah Kabupaten Labuhanbatu Pusat) - Hasugian, Fredo TSP; Syahputra, Ricky Ary; Harahap, Aulia Rahman (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
This study aims to examine the influence of local financial accountability, value for money, honesty, transparency and supervision of local financial management. The sample of this research is all SKPD (Local Work Unit Unit) as user of budget related to regional finance management at Regency Government of Labuhanbatu amounting 36 SKPD and 36 Committing Officer of Commitment so amounted 72 person. Sampling method is census method, and data used is primary data. Data were collected by distributing the queryer directly submitted to the respondent. Data analysis techniques use path analysis with the help of SmartPLS 3 program. The results of this study show that value for money, honesty, transparency and oversight have positive and significant correlation to Regional Financial Management, while Regional Financial Accountability has negative and significant correlation to Regional Financial Management.